IMPLEMENTASI MODEL PEMBELAJARAN HABIT FORMING PADA MATA PELAJARAN PAI DALAM MEMBENTUK KARAKTER SISWA DI SDN 1 LANDASAN ULIN UTARA - Siska Utami Sari; Rahmi Rabiaty (STAI AL FALAH Banjarbaru, 2025)
This research discusses the implementation of the habit-forming learning model in the subject of Islamic Religious Education (PAI) in shaping students' character at SDN 1 Landasan Ulin Utara. The purpose of this research is to evaluate the implementation of the habit-forming learning model in the subject of Islamic Religious Education (PAI) in shaping students' character, as well as to identify supporting and inhibiting factors that affect the implementation of the learning model at SDN 1 Landasan Ulin Utara. The type of this research is field research with research subjects consisting of PAI teachers and sixth-grade students. The object of this research is the implementation of the habit-forming learning model in PAI subjects in character building for students at SDN 1 Landasan Ulin Utara. Data collection was carried out through observation, interviews, and documentation techniques. The research results show that the implementation of the habit-forming learning model in the PAI subject to shape students' character at SDN 1 Landasan Ulin Utara includes several practices applied by teachers, such as greeting, reciting prayers, reading short surahs, performing congregational Dhuha prayers, performing congregational Dhuhr prayers, as well as getting used to reading Surah Yasin and Asmaul Husna, reciting the Quran, respecting differences in race, ethnicity, and religion, and valuing classmates' opinions in the learning context. Supporting and inhibiting factors in this process include Student self-readiness, good leadership and teacher examples, parental support and social environment support in the character formation process through the habit-forming learning model.